Restriction polymorphism maps of Neurospora crassa: 1998 update. - M A Nelson; M E CRAWFORD; D O NATVIG (Fungal Genetics Reports, 1998)
Restriction fragment length polymorphisms (RFLPs) can be used to determine the approximate map location of any cloned piece of DNA. To establish an RFLP mapping system for N. crassa, R.L. Metzenberg and coworkers crossed strains with multiple sequence differences, Oak Ridge laboratory strains (designated "O") and a Mauriceville-1c wild-collected strain (designated "M"; Metzenberg et al. 1984 Neurospora Newsl. 31:35-39; ibid. 1985 Proc. Natl. Acad. Sci. U.S.A.82:2067-2071; Metzenberg and Grotelueschen 1995 Fungal Genet. Newsl. 42:82-90). Progeny from two separate crosses have been widely distributed and used for mapping. For the first cross, 38 progeny from ordered asci were analyzed; since nonsister spores from the same half of the ascus were selected, first-division segregation can be distinguished from second-division. For the second cross only 18 random ascospore progeny were analyzed, and the small numbers limit resolution capabilities. Given this limitation, we encourage researchers to use the first cross for RFLP mapping. However, updated maps for both crosses are presented here.